A four‐year survey of blown pack spoilage Clostridium estertheticum and Clostridium gasigenes on beef primal cuts. (1st August 2015) - Bolton, D.J.; Carroll, J.; Walsh, D.
Abstract : Abstract: The objective of this study was to determine the incidence of Clostridium estertheticum and Clostridium gasigenes on beef primals taking sample type and season into account. Molecular methods using direct extraction of DNA without enrichment and based on the polymerase chain reaction (PCR) amplification of 16S rDNA fragments were used to test for the presence of Cl. estertheticum and Cl. gasigenes in 4826 beef primal samples (1967 drip, 1896 wet swab and 963 dry swab) provided by 10 commercial beef abattoirs over a 4‐year period. Overall 1·5% of samples were PCR positive with the incidence of Cl. estertheticum and Cl. gasigenes being 0·8 and 0·7%, respectively. Although the highest incidence of Cl. estertheticum (4·0%) and Cl. gasigenes (5·1%) was observed in June and November, respectively, seasonal differences were not significant ( P < 0·05). Drip samples yielded more positive results than swab samples. It was concluded that a low but persistent percentage of beef primal cuts are contaminated with blown pack spoilage Clostridia. There was no seasonal effect and drip may be a more effective test sample than swabs. Significance and Impact of the Study: This study provides data on blown pack spoilage contamination rates of beef primal cuts (pieces of meat initially cut from the carcass during butchering) over an extended period of time. The results show the risk of contamination is low but persistent throughout the year necessitating continuous sporicidal treatment of plant and equipment. Moreover, the higher prevalence of positive meat drip samples suggests sampling regimes should be based on this sample type.